Tindak Tutur Ekspresif dalam Novel Dua Garis Biru Karya Lucia Priandarini - Fitrianti, Bella; Juita, Novia (Universitas Negeri Padang, 2024)
The background of this research aims to describe the type of expressive submission in the novel Two Blue Lines of Lucia Priandarini's work. This type of research is qualitative using descriptive methods. The source of data used in this research is the novel Two Blue Lines. This research data is the dialogue-dialogue of the characters found in the novel two blue lines by Lucia Priandarini. Data collected by recording method. The implementation is carried out in several steps as follows: (1) classify the data according to the type of expressive follow-up in the novel Two Blue Lines by Lucia Priandarini (2) analyze the data that has been classified then interpret the data in accordance with the theory used (3) formulate conclusions based on the results of research and interpretation. Based on data analysis, eleven types of expressive behavior were identified: critical, angry, surprised, apologizing, praising, complaining, accusing, feeling happy, expressing gratitude, happiness or pleasure, and feeling ashamed. The most dominant expressive act of exaltation used in the novel Two Blue Lines is expressive expression of criticism and anger.